Vasyl Dzhevinsky: Return from Oblivion - A Pioneer in Desert Agriculture and Afforestation - Kyiak, Svitlana; Soldatenko, Halyna; Kyiak, Pavlo (Journal of Education, Health and Sport, 2023)
Background. Vasyl Mykolayovych Dzhevinsky, born in Verkhniodniprovsk in 1879, was an outstanding scientist, forester, and agronomist who laid the foundations for desert agriculture development in the Aral Sea region. His pioneering work in afforestation and plant cultivation under harsh desert conditions remained unknown in his homeland for a long time. Material and methods. The article is based on the analysis of Dzhevinsky's autobiographical manuscript covering the period from 1898 to 1953, as well as additional historical research. Results. Dzhevinsky developed an innovative method of cultivating plants in trenches in the desert, which allowed for effective afforestation and vegetable cultivation in an extremely dry climate. His work contributed to transforming the Chelkar station into a flourishing oasis, with orchards, gardens, and vineyards. Conclusions. Dzhevinsky's achievements in desert agronomy and forestry had a significant impact on agricultural development in the Aral Sea region. His story illustrates the potential of innovation in overcoming challenging environmental conditions and highlights the importance of restoring the memory of forgotten scientists.